OPTIMIZING LEARNING OUTCOMES THROUGH PROCESS-BASED DIFFERENTIATED LEARNING AT SMA POMOSDA TANJUNGANOM: AN INNOVATIVE APPROACH - Nur’aini Uswatun Hasanah; Suwito Suwito; Ika Meviana; Wawan Herry Setyawan (Prima Magistra: Jurnal Ilmiah Kependidikan, 2025)
This study aims to analyze the effect of process-based differentiation learning on student learning outcomes at SMA POMOSDA Tanjunganom. With a quantitative approach using a quasi-experimental research design, this study involved two groups: an experimental group that applied differentiated learning and a control group that used conventional methods. The study results showed that applying process-based differentiated learning can significantly improve student learning outcomes. These findings are expected to contribute to developing more effective learning methods and encourage educators to use a more responsive approach to students' needs. Process-based differentiation learning has a significant favorable influence on student learning outcomes. The research results can also provide educators insight into designing more exciting and adaptive learning strategies.